PEMBERDAYAAN SISWA SMK MELALUI PELATIHAN KETERAMPILAN DENGAN PEMANFAATAN KAIN PERCA SEBAGAI PELUANG USAHA - Askardiya Mirza Gayatri; Esti Indah Rahayu (Universitas Indraprasta PGRI, 2015)
Intellectuals educated unemployment who have graduated from vocational high school, high school, to colleges is increasing. Graduated students still oriented for looking a job, than created it. Where almost all level of education have entrepreneurship subject to study. Community service is addressed to vocational school learners (SMK), where one of their subjects in the category of adaptive group is subject Entrepreneurship. Empowerment of Class X students at SMK Respati 2, East Jakarta with training skill using patchwork, where the waste into low cost raw material, easy to find and able to make unique and interesting products with economic value and worth selling. Skill training which using participatory method and practices as well providing motivation and entrepreneurial knowledge expected to increase discourse in preparation to become entrepreneurs. The products define as brooch and accessories like bracelets. Keywords: Empowerment, skills training, patchwork, business opportunities